Exploring associations between metabolites and gene transcripts of common bean (Phaseolus vulgaris L.) in response to rust (Uromyces appendiculatus) infection - Penny Makhumbila; Molemi Rauwane; Hangwani Muedi; Ntakadzeni E. Madala; Sandiswa Figlan (BMC Plant Biology)
Abstract Common bean (Phaseolus vulgaris L.) faces escalating challenges resulting from the increasing prevalence of fungal pathogens such as rust caused by Uromyces appendiculatus, threatening yields and quality of the crop. Understanding P. vulgaris’ disease response mechanisms is pivotal for the crop’s resilience and food security. Current scientific understanding of underlying molecular mechanisms of P. vulgaris to U. appendiculatus is limited, particularly with respect to specialised molecular data, including metabolite profiles and gene expression. There is a significant knowledge gap in explicating precise metabolomic and transcriptional changes that occur in P. vulgaris upon interaction with U. appendiculatus, which limits strategies aimed at enhancing pathogen resistance. In this study, biological stress response strategies of common bean to the rust pathogen were elucidated through a combined metabolomic and transcriptomic profiling approach. Our findings revealed that U. appendiculatus triggered diverse levels of 30 known metabolites, primarily flavonoids, lipids, nucleosides, and phenylpropanoids among others. Transcriptome sequencing detected over 3000 differentially expressed genes, including multiple transcription factor families such as heat shock proteins (HSPs), cytochrome P450 monooxygenases (CYP), terpene synthases and WRKY transcription factors (TFs) among others. Integrative metabolome and transcriptome analysis showed that rust infection enriched metabolomic pathways, biosynthesis of secondary metabolites, protein processing in the endoplasmic reticulum, and purine metabolism among others. The metabolome and transcriptome integration approach employed in this study provides insights on molecular mechanisms underlying U. appendiculatus response in P. vulgaris’ key developmental stages.